The Merit and the Myth of Racial Democracy: Topics of a Discussion - Alexandre Rocha da Silva; Júlio César Augusto do Valle (Universidad Autónoma de Madrid, 2014)
We dedicate ourselves to reflect the extent to which education incorporates ideologies from alleged Brazilian racial democracy in their practices and discourses. The way such ideologies reverberate in schools is examined from theoretical located in Freire and Russell. Our discussion lies in the approach, at first historical, the social realities that produced the pernicious living conditions of the black and mulatto in Brazil. Then we show how such ideologies guiding speech and educational practices as an attempt to present mystification which educators must remain vigilant. We focus on the combination of the ideology of merit to the myth of racial democracy and also the harmful results that such articulation promotes within and outside schools. We conclude the article with a call for critical educators committed to social justice to the critics of alleged truths of capitalism through the confrontation of mystification that today pervade the lives of schools.